SISTEM INFORMASI PERPUSTAKAAN SMP SANTO LOUIS PALEMBANG - -, Ermatita (Jurnal Informatika, 2016)
The development of information technology has been absolutely used by various institutions and organizations. Library on SMP St. Louis is a unit that serves the students, and have a lot of activity such as borrowing books, serve the creation of a membership card, manage the available data books and every transaction that occurs in the library. For it will be built the library information system at SMP St. Louis. This system was developed by FAST method. The results of this study are Informs library system that manages the data in the library. Given this system will simplify the management of the library. Additionally this system will provide services to students to more easily get information about books in a library. With the existence of the library information system then reports all activity in the Library, as well as information about the existence of the book easy to navigate.Â  Keywords: FAST, Information System, libraryÂ